The Effectiveness of Finger Puppet use on Speaking Abilities of 4-5 Year-Old Children in State Kindergarten 2, Parigi Tengah Desa Matolele Village - Rafianur, Iin; Amrullah, Amrullah; Awalunisah, Sita; Fitriana, Fitriana (Journal of Educational Sciences, 2025)
This study aims to determine the effectiveness of storytelling using finger puppets on the speaking skills of early childhood students, namely vocabulary, unclear pronunciation, and the ability to answer questions. This study uses a quantitative approach with a pre-test and post-test design. The research subjects were five children in Group A. Data were obtained through observation, tests, and interviews, then analyzed using descriptive statistics and t-tests. The results of the study show an increase in children's speaking abilities after being treated with the storytelling method using finger puppets. In terms of vocabulary, the percentage of children in the Developing as Expected (BSH) category increased from 0% to 40%. In terms of pronunciation, children who initially had difficulty pronouncing words clearly began to show progress, with 40% falling into the Beginning to Develop (MB) category. Meanwhile, in terms of answering questions, although most children were still in the Beginning to Develop category, there was an increase in children's courage in giving simple answers. The t-test results showed a significance value of 0.099 > 0.05, which means that the increase was not statistically significant, but in practical terms, this method had a positive impact on the development of children's speaking skills.